2013
DOI: 10.1039/c3ta00981e
|View full text |Cite
|
Sign up to set email alerts
|

High performance asymmetric supercapacitor based on MnO2 electrode in ionic liquid electrolyte

Abstract: In this work, the electrochemical properties of a MnO 2 nanocomposite electrode were investigated in 1butyl-3-methyl-imidazolium hexafluorophosphate ([Bmim]PF 6 )/N,N-dimethylformamide (DMF) electrolyte. The [Bmim]PF 6 /DMF electrolyte with different volume fractions exhibits significant influence on the electrochemical properties of the electrode. When the volume ratio of [Bmim]PF 6 and DMF was 1 : 1, the electrode showed the best electrochemical performance. The operation potential window of the MnO 2 nanoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 43 publications
1
73
0
Order By: Relevance
“…304 For example, Zhang et al 304 found that the introduction of DMF to [BMIM][PF 6 ] IL increased the capacitance and at the same time decreased the internal resistance of the asymmetric AC//MnO 2 ES. 304 For example, Zhang et al 304 found that the introduction of DMF to [BMIM][PF 6 ] IL increased the capacitance and at the same time decreased the internal resistance of the asymmetric AC//MnO 2 ES.…”
Section: Mixtures Of Ionic Liquids and Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…304 For example, Zhang et al 304 found that the introduction of DMF to [BMIM][PF 6 ] IL increased the capacitance and at the same time decreased the internal resistance of the asymmetric AC//MnO 2 ES. 304 For example, Zhang et al 304 found that the introduction of DMF to [BMIM][PF 6 ] IL increased the capacitance and at the same time decreased the internal resistance of the asymmetric AC//MnO 2 ES.…”
Section: Mixtures Of Ionic Liquids and Organic Solventsmentioning
confidence: 99%
“…ILs have also been explored as electrolytes for hybrid ESs with asymmetric electrode configurations (e.g., AC//poly-(3-methylthiophene), 302,303 AC//MnO 2 ,304 and AC//graphene-À1 , respectively, after the first thousand cycles at 10 mA cm À2 and 60 1C. Sun et al296 used [EMIM][BF…”
mentioning
confidence: 99%
“…Firstly, the energy density of the asymmetric systems is generally higher than that of the symmetric systems due to the increased cell voltage from 0.8e1.0 V (symmetric) to 1.6e2.0 V (asymmetric). The asymmetric system combined with ionic liquid electrolyte further boosted the cell voltage to 3.0 V, and high energy density to 67.5 W h kg À1 , however, the cycling stability of such system still needs to be thoroughly understood [88]. Secondly, a rod-shaped supercapacitor assembled by two robust graphene/CNTs/MnO 2 composite films (3.2 mg, 2.2 mg cm À2 ) without metallic current collector could deliver an energy density of 2.2 W h kg À1 and a maximum power density of 42 kW kg À1 based on all the components of the packaged cell [89], which are better than that of the commercial device (0.9 W h kg À1 ; 2400 W kg…”
mentioning
confidence: 99%
“…[142,143], electrophoretic deposition [88,144], layer by layer assembly [145] and electrostatic spray deposition [146].…”
mentioning
confidence: 99%
“…10,14,15,18,[22][23][24][25][26][27][28] Among them, manganese oxides and hydroxides are of particular importance due to their low price, high theoretical specic capacitance and low toxicity. 7,10,13,23,[32][33][34][35][36][37][38][39][40][41][42] It could therefore be possible to overcome the low specic capacitance of carbon materials. 2,11,30,31 For carbon based materials incorporated with transition metal oxides, the charge storage mechanism relies on both electrical double-layer mechanisms in addition to the contribution of the redox reactions.…”
Section: Introductionmentioning
confidence: 99%